Description of the female of Cordulegaster vanbrinkae (Lohmann, 1993) (Odonata: Anisoptera: Cordulegastridae) - Holuša, Otakar (Zootaxa, 2015)
The female of Cordulegaster vanbrinkae is described and illustrated, basing on four specimens collected in Gīlān and Māzandarān Provinces, northern Iran. Their characters and variability are shown and compared with females of other Cordulegaster species.